Intuitionistic fuzzy PAMSSEM method for MAGDM incorporating cumulative prospect theory and its application to the assessment on water resource carrying capacity - Chunlan Lv; Guiwu Wei; Qing Feng; Yanli Chen; Qian Huang (PLoS ONE, 2026)
Assessing water resources carrying capacity (WRCC) is essential for regional high-quality development. However, most existing WRCC assessment models fail to handle uncertainties and mixed data arising from multiple criteria, which compromises their practical applicability. To address this limitation, this study integrates cumulative prospect theory (CPT) with the PAMSSEM outranking method to develop a novel intuitionistic fuzzy CPT-PAMSSEM model. Then the proposed method is validated through a case study of four cities in the middle and lower reaches of the Tuojiang River Basin. Results show that: (1) WRCC varies significantly across the four cities: Luzhou and Ziyang show favorable conditions, Zigong is near the critical threshold, and Neijiang faces a severe water resource shortage crisis. (2) the proposed model markedly improves the discrimination of different evaluation results, achieving a differentiation level approximately 3–6 times greater than that of conventional methods. These findings provide actionable insights for sustainable water management.